1990
DOI: 10.1111/j.1469-7610.1990.tb01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Premature Termination from Treatment among Children Referred for Antisocial Behavior

Abstract: The present study examined differences between children and families who complete treatment versus those who terminated prematurely. Children (N = 81, ages 7-13 years) referred to outpatient treatment for severe antisocial behavior and their families participated. It was predicted that families who terminate treatment prematurely would show greater dysfunction in four domains: child severity and breadth of antisocial behavior, maternal stress, maternal psychopathology, and socioeconomic disadvantage. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
4
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(164 citation statements)
references
References 28 publications
7
144
4
9
Order By: Relevance
“…Benn et al (2012) utilized a wait-list control in comparison to stress reduction and relaxation therapy, and noted that treatment and control group participants did not differ significantly at baseline. However, an analysis of parents who did not complete follow-up assessments indicated a higher baseline rate of depression, stress, and anxiety, which is common among participants who drop out of mental health interventions (Kazdin, 1990). Dykens et al (2014) chose not to use an inactive control condition by testing a two-arm intervention of mindfulness versus positive psychology.…”
Section: Methodsmentioning
confidence: 99%
“…Benn et al (2012) utilized a wait-list control in comparison to stress reduction and relaxation therapy, and noted that treatment and control group participants did not differ significantly at baseline. However, an analysis of parents who did not complete follow-up assessments indicated a higher baseline rate of depression, stress, and anxiety, which is common among participants who drop out of mental health interventions (Kazdin, 1990). Dykens et al (2014) chose not to use an inactive control condition by testing a two-arm intervention of mindfulness versus positive psychology.…”
Section: Methodsmentioning
confidence: 99%
“…Les troubles externalisés, dont les troubles des conduites et l'abus de substance sont les diagnostics qui ont été les plus associés à l'abandon du traitement chez la clientèle pédopsychiatrique (Baruch, Gerber, & Fearon, 1998;Dierker et al, 2001;El-Badri & McArdle, 1998;Kaminer et al, 1992;Kazdin, 1990;Kazdin, Mazurick, & Bass, 1993;Pagnin, de Queiroz, & Saggese, 2005;. Ces résultats n'ont toutefois pas été reproduits par qui constatent au contraire que ceux présentant des troubles de comportement ont assisté à deux fois et demie plus de séances que ceux qui ne présentent pas ces symptômes.…”
Section: Psychopathologieunclassified
“…Celle-ci n'a toutefois pas été associée de manière constante à l'abandon. Certaines études ont trouvé une corrélation positive (King et al, 1997;Siegel, Norris, & Escobar, 1994) tandis que d'autres n'ont pas trouvé d'association (Dierker et al, 2001;Kaminer et al, 1992;Kazdin, 1990).…”
Section: Psychopathologie Parentaleunclassified
“…Concurrent with results in adolescent attrition , premature termination in children was found to be more likely among children with more severe delinquent behaviors, conduct disorder, and externalizing behaviors (Baruch et al, 1998;Kazdin, 1990). …”
Section: Attrition In Child Counselingmentioning
confidence: 99%
“…Although found SES and parent relationship status were not associated with continuity of treatment, several researchers have found socioeconomic disadvantage and single parent relationship status to be associated with premature termination in children (Kazdin, 1990;Prinz & Miller, 1994). Additionally, found that children who resided in a home headed by young mothers, a non-biological parent, or a single parent were more likely to terminate counseling prematurely than those with intact two parent households.…”
Section: Attrition In Child Counselingmentioning
confidence: 99%